Customer Behavior and Perception in Financial Crisis Strategy among Bank, Fintech, and Government to Face Spread of COVID-19 - Rosana Eri Puspita; Dini Rahmayanti; Diyah Ariyani (INDEF - Institute for Development of Economics and Finance, 2021)
Collaboration between banks, fintech, and government banks is needed to overcome COVID-19. This paper aims to investigate the role of customer behavior and perception in financial crisis strategy among banks, fintech, and governments facing the unspread of COVID-19. This study used a quantitative approach with an online questionnaire as an instrument, with 178 samples retrieved. Data were analyzed by SPSS Program. The finding in this study is that Customer behavior and perception of Financial crisis strategy among banks, fintech do not influence the not spreading of COVID-19. However, the Government management crisis influenced the not spreading of COVID-19 in customer perception. The new thing in this study is the measurement of customer perception in financial crisis strategy, which applies to three institutions, i.e. bank, fintech, and government. This research concept is not done in Indonesia yet. This research suggests government push digitalization in finance to face the unspread of the COVID-19 virus. Keywords: COVID-19, financial, Fintech, Bank, Government, JEL : G20, G21, O16